Outcomes and Fate of the Distal Landing Zone Compared Between Prosthetic and Autologous Grafts After Infra-Inguinal Graft Occlusions - Rother, Ulrich; Gruber, Marc; Behrendt, Christian-Alexander; Günther, Josefine; Lang, Werner; Meyer, Alexander (Frontiers in Surgery, 2022)
Background Due to an increasing life expectancy, more and more patients experience the failure of a peripheral arterial revascularization. This study aims to investigate patients treated for failure of infra-inguinal bypass grafts, and to investigate the interaction of different bypass materials (GSV, PTFE) and the further outcome. Methods Retrospective single-center analysis of consecutive patients treated for acute or chronic occlusion of infra-inguinal bypasses at a university hospital was conducted. Hospitalizations from 1st January 2010 through 31st December 2019 were included. Perioperative parameters from the index operation including graft material (prosthetic versus autologous) were assessed. After bypass occlusion, the grade of ischemia, as well as the distal landing zone of the redo bypass compared with the primary bypass was investigated. Results 158 (65% men, 35% women, mean age 70.5 years) eligible patients were included (57% vein, 42% prosthetic bypass grafts). After graft occlusion, 47% of the patients presented with symptoms of an acute limb-threatening ischemia, 53% with symptoms of chronic leg ischemia. The rate of acute limb-threatening ischemia was significantly higher when prosthetic graft material was used during the index operation (p= 0.016). Additionally, in case of reoperation, the landing zone of the redo bypass was significantly more distally located after occlusion of a prosthetic bypass graft (p=0.014) Conclusion Occlusions of prosthetic bypass grafts were associated with significantly higher rates of acute symptoms compared with vein grafts. Additionally, a shift to a more distal landing zone was recognized after failure of a prosthetic bypass graft during the redo bypass operation.